Use of intravitreal bevacizumab or triamcinolone acetonide as a preoperative adjunct to vitrectomy for vitreous haemorrhage in diabetics - Ferraz,Daniel Araújo (2013)
PURPOSE: To evaluate the effect of preoperative intravitreal bevacizumab (IVB) or triamcinolone (IVT) on the rate of early postvitrectomy hemorrhage in proliferative diabetic retinopathy (PDR). METHODS: Eligible eyes were assigned randomly to 1 of 3 groups: the IVB group received 1.25 mg bevacizumab, the IVT group received 4,0mg triamcinolone and the control group underwent a sham procedure. The primary outcome measure was the incidence of early postvitrectomy hemorrhage. Secondary outcome measures included changes in visual acuity (BCVA) and adverse events. RESULTS: Twenty and seven eyes, 9 in each group were randomized. The incidence of vitreous hemorrhage was lower in the IVB group (p=0.18). Postoperative vitreous hemorrhage at 1 month also was less in the IVB group compared with the control group (p > 0.05). The rate of bleeding immediately after surgery was higher in IVT group with 4 (44.4%) cases. The overall mean visual acuity was 1.72 ± 0.37 logMAR preoperatively and 1.32 ± 0.73 logMAR in 6 months after surgery. Accessing visual acuity by group evidenced that the IVB group had initial mean logMAR VA of 1.87 and 1.57 logMAR VA at the six months (p = 0.84). In IVT group, initial mean VA was 1.75 logMAR and 0.96 logMAR VA at six months (p < 0.001). And in control group, the initial mean VA was 1.85 logMAR and 1.57 logMAR VA at six months (p= 0.34). CONCLUSION: Intravitreal injection of bevacizumab 1 week before vitrectomy seems to reduce the incidence of early postvitrectomy hemorrhage in diabetic patients. There was a better visual acuity outcome in the triamcinolone group.